Liver histology and diffusion‐weighted MRI in children with nonalcoholic fatty liver disease: A MAGNET study. Issue 4 (22nd February 2017) - Manning, Paul; Murphy, Paul; Wang, Kang; Hooker, Jonathan; Wolfson, Tanya; Middleton, Michael S.; Newton, Kimberly P.; Behling, Cynthia; Awai, Hannah I.; Durelle, Janis; Paiz, Melissa N.; Angeles, Jorge E.; et al.
Abstract : Purpose: To determine potential associations between histologic features of pediatric nonalcoholic fatty liver disease (NAFLD) and estimated quantitative magnetic resonance diffusion‐weighted imaging (DWI) parameters. Materials and Methods: This prospective, cross‐sectional study was performed as part of the Magnetic Resonance Assessment Guiding NAFLD Evaluation and Treatment (MAGNET) ancillary study to the Nonalcoholic Steatohepatitis Clinical Research Network (NASH CRN). Sixty‐four children underwent a 3T DWI scan (b‐values: 0, 100, and 500 s/mm 2 ) within 180 days of a clinical liver biopsy of the right hepatic lobe. Three parameters were estimated in the right hepatic lobe: apparent diffusion coefficient (ADC), diffusivity (D), and perfusion fraction (F); the first assuming exponential decay and the latter two assuming biexponential intravoxel incoherent motion. Grading and staging of liver histology were done using the NASH CRN scoring system. Associations between histologic scores and DWI‐estimated parameters were tested using multivariate linear regression. Results: Estimated means ± standard deviations were: ADC: 1.3 (0.94–1.8) × 10 −3 mm 2 /s; D: 0.82 (0.56–1.0) × 10 −3 mm 2 /s; and F: 17 (6.0–28)%. Multivariate analyses showed ADC and D decreased with steatosis and F decreased with fibrosis ( P < 0.05). Associations between DWI‐estimated parameters and other histologic features were not significant: ADC: fibrosis ( P = 0.12), lobular inflammation ( P = 0.20), portal inflammation ( P = 0.27), hepatocellular inflammation ( P = 0.29), NASH ( P = 0.30); D: fibrosis ( P = 0.34), lobular inflammation ( P = 0.84), portal inflammation ( P = 0.76), hepatocellular inflammation ( P = 0.38), NASH ( P = 0.81); F: steatosis ( P = 0.57), lobular inflammation ( P = 0.22), portal inflammation ( P = 0.42), hepatocellular inflammation ( P = 0.59), NASH ( P = 0.07). Conclusion: In children with NAFLD, steatosis and fibrosis have independent effects on DWI‐estimated parameters ADC, D, and F. Further research is needed to determine the underlying mechanisms and clinical implications of these effects. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017;46:1149–1158.